2022
DOI: 10.1002/hbm.26013
|View full text |Cite
|
Sign up to set email alerts
|

The age‐related changes in 40 Hz Auditory Steady‐State Response and sustained Event‐Related Fields to the same amplitude‐modulated tones in typically developing children: A magnetoencephalography study

Abstract: Recent studies have revealed that gamma-band oscillatory and transient evoked potentials may change with age during childhood. It is hypothesized that these changes can be associated with a maturation of GABAergic neurotransmission and, subsequently, the age-related changes of excitation-inhibition balance in the neural circuits. One of the reliable paradigms for investigating these effects in the auditory cortex is 40 Hz Auditory Steady-State Response (ASSR), where participants are presented with the periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…We indeed found that phase locking to the auditory stimulation at 40 Hz were associated with cortical myelination in the right cerebellum, more specifically the right Crus I. While the cortical generator of the ASSR is typically seen spreading over the auditory areas (temporal regions) (Arutiunian et al, 2022;Farahani et al, 2021) and cerebellum (Pastor et al, 2002), the frontal areas are also involved in the mismatch negativity responses (Garrido et al, 2009). Our results therefore suggest that within the same areas generating the 40 Hz ASSR, the ability to phase lock to the 40 Hz auditory stimulation is associated with the degree of myelination within those regions.…”
Section: Structure-function Relationshipmentioning
confidence: 59%
“…We indeed found that phase locking to the auditory stimulation at 40 Hz were associated with cortical myelination in the right cerebellum, more specifically the right Crus I. While the cortical generator of the ASSR is typically seen spreading over the auditory areas (temporal regions) (Arutiunian et al, 2022;Farahani et al, 2021) and cerebellum (Pastor et al, 2002), the frontal areas are also involved in the mismatch negativity responses (Garrido et al, 2009). Our results therefore suggest that within the same areas generating the 40 Hz ASSR, the ability to phase lock to the 40 Hz auditory stimulation is associated with the degree of myelination within those regions.…”
Section: Structure-function Relationshipmentioning
confidence: 59%
“…Ear lobe electrodes were used as reference and the grounding electrode was placed centrally. The signal was sampled at 500 Hz and filtered online with a bandpass filter of 0.016-70 Hz, which enabled us to detect our effects of interest, as a higher lowpass filter was used in previous studies 25,45 and to reject some low-frequency artifacts at the same time. This lowpass filter (0.016 Hz) is the lowest frequency that is implicated in many clinical devices; however, this setting is sufficient to detect both parameters of interest.…”
Section: Eeg Recordingsmentioning
confidence: 99%
“…ASSR is hardly detected at an early age and increases later in neurotypical children, 23,36,44 whereas SW is clearly registered in young children. 25,45 As children with RTT have an abnormal developmental trajectory, it would be useful to investigate the age dynamics of these responses. ASSR can indicate clinical progression, whereas SW impairment might point to abnormalities at a very young age.…”
mentioning
confidence: 99%
“…1 The avant-garde results from published studies seem to be variable and controversial owing to factors including age, hearing condition, types/sides of stimulation, stimulus repetition rate, carrier frequency of stimuli, and recording methodology. 8,[10][11][12][13][14][15][16] Although previous studies revealed a tendency for the SSAERs to be right-side dominant under predetermined circumstances, 10,17 the hemispheric asymmetry for the magnetic counterpart of SSAERs (ie, steady-state auditory evoked fields [SSAEFs]) induced by parameters reasonably accessible clinically has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%